INFLUENCE AND STRATEGY OF CUSTOMER RELATIONSHIP MANAGEMENT ON CUSTOMER SATISFACTION AND CUSTOMER LOYALTY IN MICRO AND MEDIUM ENTERPRISES - Sania Imalia Qalbi; Arianis Chan; Cecep Safa'atul Barkah; Pratami Wulan Tresna (Jurnal Ilmiah Ekonomi Bisnis, 2022)
A good and growing business is a business that has loyal customers. Loyal customers are one of the reasons why businesses can grow rapidly and stay long standing. Loyal customers are not only about repeat purchases, but with satisfaction and referring to others is also a form of loyal customers. This is felt by Benari, a local fashion brand that is currently developing. Even though they have experienced it, Benari still feels that customer loyalty in Benari is still low. Therefore, it is studied through Customer Loyalty analysis and looking for strategies to increase Customer Loyalty. The analytical method of this research uses a quantitative descriptive approach, with data sources through Focus Group Discussion, questionnaires with 152 respondents, and literature review. The results of this study indicate that customer loyalty in Benari is very good, but still requires a strategy to increase customer loyalty. This strategy can be pursued through flash sales and cross selling strategies. By implementing this strategy, it is hoped that Benari can increase customer loyalty and sales